2006
DOI: 10.1158/0008-5472.can-05-2508
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer DNA Methylation Profiles in Cancer Cells and Tumor Stroma: Association with HER-2/neu Status in Primary Breast Cancer

Abstract: The HER-2/neu gene is amplified and overexpressed in 20% to 30% of invasive breast carcinomas and is associated with increased metastatic potential and less tamoxifen sensitivity. We generated the DNA methylation profiles of 143 human breast tumors and found significant differences in HER-2/ neu expression and DNA methylation of five genes. For three of these five genes [PGR (coding for the progesterone receptor), HSD17B4 (coding for type 4 17-B-hydroxysteroid dehydrogenase, an enzyme that mainly degrades acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
116
3
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 22 publications
10
116
3
3
Order By: Relevance
“…Previous studies have reported the association of DNA methylation patterns with molecular subtypes of breast cancer through hormone receptor and HER2/neu status. [14][15][16][17]35 In an early study by Sunami et al, 14 double-negative (ER-negative, HER2/neunegative) breast cancers, corresponding to the basal-like subtype, were reported to have lower frequencies of RASSF1A, GSTP1, and APC methylation, and this was confirmed in the present study. Suijkerbuijk et al 36 examined the methylation of 11 genes involved in breast carcinogenesis (RARB, RASSF1, TWIST, CCND2, ESR1, SCGB3A1, BRCA1, BRCA2, CDKN2A, APC, CDH1) by quantitative multiplex methylation-specific PCR in BRAC1-associated and sporadic breast cancers, and showed that the median values for RASSF1, TWIST, SCGB3A1, APC, and the cumulative methylation index for the 11 genes, were significantly lower in BRAC1-associated hereditary breast cancers than in sporadic ones.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have reported the association of DNA methylation patterns with molecular subtypes of breast cancer through hormone receptor and HER2/neu status. [14][15][16][17]35 In an early study by Sunami et al, 14 double-negative (ER-negative, HER2/neunegative) breast cancers, corresponding to the basal-like subtype, were reported to have lower frequencies of RASSF1A, GSTP1, and APC methylation, and this was confirmed in the present study. Suijkerbuijk et al 36 examined the methylation of 11 genes involved in breast carcinogenesis (RARB, RASSF1, TWIST, CCND2, ESR1, SCGB3A1, BRCA1, BRCA2, CDKN2A, APC, CDH1) by quantitative multiplex methylation-specific PCR in BRAC1-associated and sporadic breast cancers, and showed that the median values for RASSF1, TWIST, SCGB3A1, APC, and the cumulative methylation index for the 11 genes, were significantly lower in BRAC1-associated hereditary breast cancers than in sporadic ones.…”
Section: Discussionsupporting
confidence: 85%
“…7 There are reports that promoter CpG island hypermethylation is associated with various histopathologic characteristics of breast cancers, including histologic type, 10,11 tumor grade, 12,13 hormone receptor, and HER2/neu status. [14][15][16][17] Array-based comprehensive DNA methylation profiling has shown that breast cancer molecular subtypes have their own methylation profiles. [18][19][20][21] Moreover, these different methylation profiles were evident throughout the CpG islands of the genome, not limited to functional genes.…”
mentioning
confidence: 99%
“…Our data show that although somatic alterations can occur in CAFs, they are exceedingly rare and are unlikely to be responsible for the stable cancer-promoting attributes of CAFs. However, our findings cannot exclude the possibility that other mechanisms, such as epigenetic changes, have a role in the tumor-promoting phenotype of CAFs 18,25 .…”
contrasting
confidence: 56%
“…Some authors think that MTCs come directly from cancer cells as a consequence of epithelialmesenchymal transition (Petersen et al, 2001;Pennacchietti et al, 2003;Knutson et al, 2006;Thiery and Sleeman, 2006). An alternative explanation is that MTCs derive from preexisting stromal fibroblasts or their precursors, following microenvironmentally induced 'epigenetic changes' (Kurose et al, 2002;Hu et al, 2005;Fiegl et al, 2006).…”
Section: Discussionmentioning
confidence: 99%